Advances in ophthalmic optics technology - Lima Monteiro, Davies William de, 1972-; Cançado Trindade, Bruno Lovaglio (IOP (Series). Release 22., 2022)
This book bridges the gap between the clinical practice and the engineering of lens design. It explores advances in refractive correction in ophthalmic optics, with a focus on current and future intraocular lenses, and presents challenges for lenses with premium features as extended depth of focus and integrated functions.